Literature About Maintaining Physical Fitness Through Digital in Community - Zharfan M Salman; Asep Bayu Dani Nandiyanto (Universitas Komputer Indonesia, 2022)
This study aims to educate the public on how to maintain good and correct physical fitness, starting from the basic understanding, to how important it is, to how to implement it in everyday life where using digital methods in society. Education was carried out to the community members in RT 04, RW 02, Cibabat output, using the digital literacy method, namely providing information and learning through digital media to explain to the subject. The information given to the community subjects is made as concise as possible and interesting so that it is easily understood by the community. The education process is carried out online by using whatsapp and zoom meetings, while offline by conducting direct socialization to the community. The understanding of the community was analyzed through pretest and posttest questions, totaling 20 questions. The results of this study indicate that there is an increase in the score from pretest to posttest. The education provided is able to make the public understand the subject of the given theme. This shows that educational activities are successful because the information conveyed to the public can generate public interest in understanding the information that has been provided. This research can provide information that digital media can be used both as a tool for education and can increase public interest in adding new knowledge